Carotid body hyperplasia and enhanced ventilatory responses to hypoxia in mice with heterozygous deficiency of PHD2. (18th July 2013) - Bishop, Tammie; Talbot, Nick P.; Turner, Philip J.; Nicholls, Lynn G.; Pascual, Alberto; Hodson, Emma J.; Douglas, Gillian; Fielding, James W.; Smith, Thomas G.; Demetriades, Marina; Schofield, Christopher J.; Robbins, Peter A.; et al.
Key points: Arterial hypoxaemia leads to a rapid increase in ventilation. If the hypoxaemia is sustained, a further increase in ventilation develops over hours to days in a process termed ventilatory acclimatisation. Studies in transgenic mice implicate the hypoxia‐inducible factor (HIF) pathway in the latter process. The aim of this study was to investigate the role of HIF prolyl hydroxylase (PHD) enzymes in ventilatory acclimatisation. We find that PHD2 +/−, but not PHD1 −/− or PHD3 −/−, mice mimic chronic hypoxia in exhibiting exaggerated ventilatory responses to acute hypoxia. This was associated with carotid body overgrowth. However, use of a PHD inhibitor (PHI) induced both hypoxic ventilatory sensitivity and carotid body proliferation only marginally despite strongly inducing erythropoiesis. Taken together, these findings implicate HIF/PHD2 in ventilatory control and carotid body biology but highlight the difficulty of translation from genetic models to pharmacological intervention. Abstract Oxygen‐dependent prolyl hydroxylation of hypoxia‐inducible factor (HIF) by a set of closely related prolyl hydroxylase domain enzymes (PHD1, 2 and 3) regulates a range of transcriptional responses to hypoxia. This raises important questions about the role of these oxygen‐sensing enzymes in integrative physiology. We investigated the effect of both genetic deficiency and pharmacological inhibition on the change in ventilation in response to acute hypoxic stimulation in mice. Mice exposed to chronic hypoxia for 7 days manifest an exaggerated hypoxic ventilatory response (HVR) (10.8 ± 0.3 versus 4.1 ± 0.7 ml min −1 g −1 in controls; P < 0.01). HVR was similarly exaggerated in PHD2 +/− animals compared to littermate controls (8.4 ± 0.7 versus 5.0 ± 0.8 ml min −1 g −1 ; P < 0.01). Carotid body volume increased (0.0025 ± 0.00017 in PHD2 +/− animals versus 0.0015 ± 0.00019 mm 3 in controls; P < 0.01). In contrast, HVR in PHD1 −/− and PHD3 −/− mice was similar to littermate controls. Acute exposure to a small molecule PHD inhibitor (PHI) (2‐(1‐chloro‐4‐hydroxyisoquinoline‐3‐carboxamido) acetic acid) did not mimic the ventilatory response to hypoxia. Further, 7 day administration of the PHI induced only modest increases in HVR and carotid body cell proliferation, despite marked stimulation of erythropoiesis. This was in contrast with chronic hypoxia, which elicited both exaggerated HVR and cellular proliferation. The findings demonstrate that PHD enzymes modulate ventilatory sensitivity to hypoxia and identify PHD2 as the most important enzyme in this response. They also reveal differences between genetic inactivation of PHDs, responses to hypoxia and responses to a pharmacological inhibitor, demonstrating the need for caution in predicting the effects of therapeutic modulation of the HIF hydroxylase system on different physiological responses.